Law firm librarianship : issues, practice, and directions - Azzolini, John (Chandos information professional series., 2013)
The legal information environment is deep, wide, and dynamic with many participants, including courts, parliaments, legislatures, and administrative bodies. None exemplifies the agile, knowledge-engaging legal player better than the law firm. Current, authoritative information is essential for the successful representation of clients. The firm's most dependable resource for retrieving information is its library staff. Law Firm Librarianship introduces the reader to the challenges, qualifications, and work conditions of this distinct type of research librarian. The book begins by asking what law firm librarianship is, whilst the second chapter focuses on the law firm and its culture. The third chapter covers the law firm library itself, including the practical aspects of the firm librarian's interaction with his or her professional environments. The next chapter considers the effects of legal publishing practices, and the penultimate section surveys the various research tools the firm librarian relies on for sound knowledge. The book concludes by looking at the dynamic qualities of law firm librarianship. Offers an up-to-date overview from an experienced practitionerAdds to the library literature by addressing a type of librarianship that usually receives little attentionApplies field knowledge about legal information trends that will inform related areas of inquiry.